31.2k views
5 votes
5.Write each algebraic expression in simplest form.

a. (5x - 3y) + (7x + 4y)

Can y’all help me

2 Answers

0 votes

Answer:

12x + y

Explanation:

(5x - 3y) + (7x + 4y)

-you need to distribute a 1 from the 1(7x + 4y) and drop the 5x - 3y

5x - 3y + 7x + 4y

- combine like terms

5x + 7x = 12x & -3y + 4y = 1y or just y

12x + y

User Fieldtensor
by
5.4k points
4 votes

Answer:

=12x+y

Explanation:

Combine like terms

=5x+-3y+7x+4y

=(5x+7x)+(-3y+4y)

=12x+y

User LimeRed
by
4.7k points